Digital Storytelling Improves Cognitive Skills in Preschool Children: Cerita Digital Meningkatkan Keterampilan Kognitif pada Anak-Anak Pra-Sekolah - Faridatun Muamaroh; Evie Destiana (Academia Open, 2025)
General Background: Early Childhood Education (ECE) plays a crucial role in optimizing multiple domains of child development, particularly cognitive abilities related to thinking, understanding, memory, and problem-solving. Specific Background: Children aged 5–6 years require engaging learning environments and appropriate stimulation to support emerging skills such as critical thinking, collaboration, and cause-and-effect reasoning. Knowledge Gap: Observations at RA Darul Arqom indicated that several children showed suboptimal cognitive performance, partly due to conventional teaching methods that lacked attractiveness and interactivity. Aims: This study aimed to examine the use of digital storytelling as a learning medium for children aged 5–6 years using a quantitative one-group pretest–posttest design. Results: Findings revealed a substantial rise in posttest scores compared with pretest results after the intervention. Statistical analysis showed normally distributed data (Sig. = 0.257), a significant F value (p = 0.000), and a significant t-test result (p < 0.05), indicating meaningful improvement in critical thinking, problem-solving, and understanding of causal relationships. Novelty: The study demonstrates the practical application of multimedia-based storytelling integrating visual, audio, text, and animation elements within an authentic preschool setting. Implications: Digital storytelling can serve as an innovative instructional strategy aligned with 21st-century learning demands, supporting early cognitive growth and preparing children for subsequent educational stages. Highlights: Post-intervention scores were markedly higher than baseline measurements. Children demonstrated stronger reasoning, questioning, and collaboration abilities. Statistical testing confirmed a significant difference between initial and final observations. Keywords: Digital Storytelling; Cognitive Development; Early Childhood Education; Preschool Children; Multimedia Learning